Pengaruh Ion Kadmium(II) dan Nikel(II) pada Ekstraksi Ion Tembaga(II) dengan Ekstraktan 4-Benzoil -1-Fenil-3-Metil- 2- Pirazolin-5-On Menggunakan Emulsi Membran Cair - Hamzah, Baharuddin; Jalaluddin, Noor; Wahab, Abdul Wahid; Upe, Ambo (Jurnal Natur Indonesia, 2011)
The effects of cadmium(II) and nickel(II) ions to copper(II) extraction using liquid membrane emulsion with 4-benzoyl-3-methyl-1-phenyl-2-pyrazolin-5-on (HPMBP) as an extractant was studied. The optimum condition forcopper(II) extraction were as follows: emulsification rate=2000 rpm, emulsification time=10 minutes, extractionrate=300 rpm, extraction time=15 minutes, concentration of mixed surfactant (span 80+span 20)=3%, volumeratio of membrane phase and internal phase=1:1, concentration of HPMBP=0.020 M, concentration of HCl=1M,volume ratio of emulsion and external phase=1:7. The result showed that the extraction of copper(II) by liquidmembrane emulsion with HPMBP as an extractant was selective to cadmium(II) and nickel(II) ions, relatively. Theresult also showed that in the extraction of 500 mg/l copper(II), the presence of 500 mg/l of nickel(II) was decreasingthe percentage of copper(II) extraction to be 83.73. While, the presence of 500 mg/l of cadmium(II) does notinfluence the percentage extraction of copper(II), relatively.